2016
DOI: 10.12809/hkmj154566
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic changes in emergency department patients with poorly controlled hypertension

Abstract: Objectives: This study aimed to measure cardiac output, systemic vascular resistance, cardiac index, and systemic vascular resistance index in emergency department patients with poorly controlled hypertension; and to determine the frequency in which antihypertensive drugs prescribed do not address the predominant haemodynamic abnormality. Methods:This cross-sectional observational study was conducted in an emergency department of a 1400-bed tertiary hospital in Hong Kong. Patients aged 18 years or above, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…32,101,103,[107][108][109] In patients with hypertension, SVR was elevated in almost 66% of cases. 117 It was reported that high normal BP (130-139/85-89 mmHg) progresses to…”
Section: Ke9 (Increased Vascular Resistance) To Ao (Hypertension)mentioning
confidence: 99%
See 2 more Smart Citations
“…32,101,103,[107][108][109] In patients with hypertension, SVR was elevated in almost 66% of cases. 117 It was reported that high normal BP (130-139/85-89 mmHg) progresses to…”
Section: Ke9 (Increased Vascular Resistance) To Ao (Hypertension)mentioning
confidence: 99%
“…51,115,116 In patients with hypertension, SVR was elevated in about 66% of enrolled patients. 117 KERs, key event relationships. Rating is high due to extensive and consistent evidence.…”
Section: Highmentioning
confidence: 99%
See 1 more Smart Citation